AUDIT KOMUNIKASI DI UNP (Kasus : Komunikasi Lintas Saluran Antara BAAK dan Puskom Universitas Negeri Padang) - Hasmira, Mira Asti (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2012)
This study aims to uncover the causes and solutions to the discrepancy of information from BAAK and Puskom of State University of Padang (UNP). Hence, students often have to revisits both institutions when dealing with an administration problem. In this study, researcher uses the standard form of communication experience to measure communication audit conducted. Measurement standard was chosen because it is considered most appropriate to the communication audit to be conducted. The study found that the causes of the discrepancy of information between BAAK and Puskom UNP are Personal Factors (selective perception, some imprecise phrases) and Organizational Factors (status or position in the organization, prestige). This does not supposed to happen because as a formal organization, UNP have Standard Operational Procedure (SOP) to handle problems concerned with BAAK and Puskom. Kata kunci : communication audit, information discrepancy, Puskom UNP, BAAK UNP